Knowledge, Perception, and Public Attitude on Biotech Crops in Indonesia - Dahri Tanjung; Yeti Lis Purnamadewi; Bambang Purwantara; Dewi Suryani (Jurnal Mamangan, 2023)
Until now, many genetically engineered products have met our basic needs and provided various economic, environmental, and health benefits. However, there are still many who doubt or even oppose them. This raises the question of how the public's knowledge and understanding of these biotechnological plants stand. Consequently, this condition will affect the varied attitudes of society. Thus, this research aims to analyze whether public actions in adopting biotechnology are significantly influenced by their knowledge and perceptions. This survey uses a questionnaire and was conducted with 535 respondents from several provinces. The results show that around 70% of respondents have limited knowledge about biotechnology. The information channels they use include print media, social media, and interpersonal communication. About 75% of respondents agree or strongly agree that biotechnology can enhance agricultural productivity, the economy, and farmers' welfare, and contribute to food security. Furthermore, 76% of respondents agree to purchase these products. Despite the above findings, the lack of information regarding genetically engineered plants has led a majority of Indonesians to feel "neutral" about the risks they perceive regarding health and the environment. PLS-SEM analysis reveals a strong positive relationship between knowledge, perceptions, and positive attitudes toward biotechnology products. Therefore, factors such as enhancing information dissemination through various alternative media and involving stakeholders need to be intensified for the future development of biotechnology